Effect of Piecemeal vs En Bloc Approaches to the Lateral Temporal Bone on Survival Outcomes. (April 2018) - Muelleman, Thomas; Chowdhury, Naweed I.; Killeen, Daniel; Sykes, Kevin; Kutz, J. Walter; Isaacson, Brandon; Staecker, Hinrich; Lin, James
Objectives: Lateral temporal bone resection (LTBR) has traditionally been performed en bloc in accordance with oncologic principles. Occasionally, this is not possible due to a low tegmen or lateralized vasculature. We sought to determine if outcomes of piecemeal and en bloc LTBR are comparable. Study Design: Retrospective review. Setting: Two academic medical centers. Subjects and Methods: Multi-institutional retrospective cohort study. Current Procedural Terminology codes were used to identify patients with T1 to T3 squamous cell carcinoma of the external auditory canal (EAC) who underwent LTBR from 2005 to 2015. Kaplan-Meier curves were constructed to compare total survival between the 2 treatment approaches. Pairwise comparisons were performed using χ 2 and Fisher exact tests (significance at P = .05), as appropriate. Results: Twenty-five patients were identified. Ten patients underwent en bloc LTBR; 15 underwent piecemeal LTBR. Median follow-up time was 11 months (range, 1-60 months). There was not a significant difference in overall survival between en bloc (38.9 months; 95% confidence interval [CI], 22.7-55.2) compared to piecemeal (37.5 months; 95% CI, 21.1-53.9) procedures ( P = .519). Estimates of disease-free survival also did not reveal statistically significant differences: estimated mean disease-free survival was 48.1 months (95% CI, 33.7-62.6) in en bloc patients and 32.5 months (95% CI, 17.1-47.8) in piecemeal patients ( P = .246). Conclusion: These data suggest that piecemeal resection can be considered for cases of squamous cell carcinoma involving the external auditory canal where anatomic constraints preclude a safe en bloc resection. Larger studies or studies with a longer follow-up time may provide improved insight into survival comparisons.